2005
DOI: 10.1063/1.1894582
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electrical properties of sol-gel-derived (001)-oriented Pb[Yb1∕2Nb1∕2]O3–PbTiO3 thin films grown on LaNbO3∕Si(001) substrates

Abstract: ( 1 − x ) Pb [ Yb 1 ∕ 2 Nb 1 ∕ 2 ] O 3 – x Pb Ti O 3 (PYbN–PT, x=0.5) oriented thin films were deposited onto LaNiO3 (LNO)∕Si substrates by sol-gel processing. Highly (001)-oriented LNO thin films were prepared by a simple metal-organic decomposition technique when sample annealed at 650°C using a rapid thermal annealing. The room-temperature resistivity of LNO thin films was 0.65mΩcm. X-ray diffraction analysis revealed that the films of PYbN–PT were highly (001) oriented along LNO∕Si substrates. No pyrochlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, the change in the resistivity is very small when the film is thicker than 150 nm. The measurements showed that the resistivity of the LNO films with thickness of 150 nm was 9.27 Â 10 À6 O m, which is of the same order as those of films obtained by the same wet chemical process [5,16,17] and other physical processes [10,11]. Therefore, the LNO thin films with 150 nm thickness annealed at 600 1C can be selected as electrodes for the growth of ferroelectric thin films.…”
Section: Electrical Properties Of Lno Filmsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the change in the resistivity is very small when the film is thicker than 150 nm. The measurements showed that the resistivity of the LNO films with thickness of 150 nm was 9.27 Â 10 À6 O m, which is of the same order as those of films obtained by the same wet chemical process [5,16,17] and other physical processes [10,11]. Therefore, the LNO thin films with 150 nm thickness annealed at 600 1C can be selected as electrodes for the growth of ferroelectric thin films.…”
Section: Electrical Properties Of Lno Filmsmentioning
confidence: 98%
“…Lanthanum nickel oxide (LaNiO 3 :LNO) film has attracted great attention in recent years for its promising application as a bottom electrode in the fabrication of ferroelectric memories and integrated ferroelectric microelectro-mechanical systems (MEMS) devices with silicon semiconductor technology, because it can improve ferroelectric fatigue properties of the ferroelectric films [1][2][3][4][5]. LNO is a perovskite-type metallic oxide with a pseudocubic lattice parameter of 0.384 nm, which matches well with that of most ferroelectric films, such as PbTiO 3 , Pb(Zr, Ti)O 3 , BaTiO 3 and (Ba, Sr)TiO 3 , and its resistivity at room temperature is about 10 À6 O m [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…T HERE has been an increasing interest in ferroelectric thin films such as lead zirconate titanate (PZT) because of their potential applications as micro-actuators, sensors in microelectromechanical systems (MEMS), and non-volatile ferroelectric random access memories (FRAM). [1][2][3] In addition to high ferroelectric and piezoelectric performances, good temperature stability is very important in device applications as well, especially in automotive, aerospace, and related industries. It has been reported that the temperature stability of ferroelectric thin films is mainly determined by the ferroelectric-paraelectric transition temperature (T c ).…”
Section: Introductionmentioning
confidence: 99%
“…After that, Bi(NO) 3 was dissolved in the solution, and distilled water with the same volume as the glacial acid was added. Subsequently, Pb(COOCH 3 ) 2 and Sc(COOCH 3 ) 3 were dissolved into the solution. Finally, an appropriate formamide was added into the above solution to prevent the appearance of cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Of the known relaxor ferroelectric-PbTiO 3 solid solutions, PYbN-PT has the highest transition temperature (∼360 °C) at the MPB composition ( x =0.5) [15]. A chemical solution deposition process for (111) and (001) oriented films on Pt/Si substrate were recently reported [17]. It was observed that (001) oriented thin films have better piezoelectric properties (e 31,f coefficients of −8.2 C/m 2 ) than (111) oriented PYbN-PT thin films (e 31,f coefficients of −4.8 C/m 2 ).…”
Section: Introductionmentioning
confidence: 99%